A dynamic model of the Perak welfare program towards zero rated poverty - Hanis Dalila, Faizal (2024)
Perak has implemented many programs to tackle poverty issues. Despite various programs, the poverty rate in Perak is still among the highest rate in Malaysia. Therefore, there is a need to understand the interplay of factors contributing to poverty and identify the most effective strategies for poverty eradication. This study develops a system dynamics model to evaluate the impact of the Perak Welfare Program on achieving a zero-poverty rate. The model incorporates feedback loops and time-dependent relationships among key factors such as education, income, employment, and welfare interventions. Using Vensim software, a stock-and-flow model was developed to simulate the dynamic behavior of poverty under different policy scenarios. Data for the model were drawn from both primary and secondary sources, including interviews with program officers and government reports. The findings reveal that long-term investments in education and employment schemes yield the most significant reductions 90.6% in poverty, outperforming short-term measures such as direct financial aid. By revising budget allocations based on the sensitivity analysis and implementing targeted interventions, the study demonstrates that a coordinated and data-driven approach can effectively break the poverty cycle in Perak. The developed model provides clear perspective into the complex dynamics of poverty reduction, offering policymakers a robust tool for designing and evaluating welfare strategies in achieving equitable and impactful poverty eradication outcomes.